EFFECT OF USING PORTFOLIO ASSESSMENT TO IMPROVE SCIENTIFIC ATTITUDE OF STUDENTS LEARNING PHYSICS IN HIGH SCHOOL - wartawan, putu (LPPM Undiksha, 2017)
This study aims to investigate the effect of portfolio assessment in teaching physics and scientific attitude. The research was conducted on students of high schoolÂ in Singaraja. Research was anÂ quasi- experimental study by usingÂ âThe Posttest-Only Control Group Designâ.Â The research involved 152 high school students of class X of science as samples, taken with multistage random sampling technique. Portfolio assessment was integrated with physics learning. The implementation of the portfolio assessment included four key elements such as the students work folders, clear assessment criteria, and self-assessment, and conference between teacher and students.Â The data needed in this research was the students scientific attitude which included the aspect of curiosity, respect for evidence, the willingness to change ideas, and critical reflection. Data needed in this research included scientific attitudes students.Â A Likert scale instrument was used to measure the scientific attitude students.Â Data were analyzed usingÂ analysis of variance with SPSS 20.0 at significance level a = 0.05. The results showed there are differences in the scientific attitude students who take physics learning with assessment portfolios and students who take physics learning with assessment of conventional.Â The findings of this study indicate that portfolio assessment in learning physics significantly affect the scientific attitude students.